1999
DOI: 10.1111/j.1751-1097.1999.tb03348.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sensitivity to UVC, UVB and UVA Radiation of a Multidrug‐Resistant Cell Line Overexpressing P‐Glycoprotein

Abstract: Multidrug resistance (MDR) is the phenomenon in which cultured tumor cells, selected for resistance to one chemotherapeutic agent, simultaneously acquire resistance to several apparently unrelated drugs. The MDR phenotype is multifactorial. The best-studied mechanism involves the expression of a membrane protein that acts as an energy-dependent efflux pump, known as P-glycoprotein (Pgp), capable of extruding toxic materials from the cell. In this work, resistance to UVA radiation, but not to UVC nor UVB, was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
5
30
0
1
Order By: Relevance
“…Many authors have suggested that the acquisition of the MDR phenotype is accompanied by modifications of the cytoskeleton such as increased expression of actin and/or tubulin and alterations on the organisation of stress fibres, microtubules and the Golgi complex (Lee et al 1993, Lee 1995, Seidel et al 1995, Erokhina et al 1994. In agreement with these observations, Lucena 1 cells were shown to express higher levels of actin m-RNA and of the proteic subunits a and b-tubulin, when compared to the parental K562 (Trindade et al 1998). It is still unclear the role played by the modifications observed in the cytoskeleton on the MDR phenotype.…”
Section: Alterations Of the Cytoskeletonsupporting
confidence: 70%
“…Many authors have suggested that the acquisition of the MDR phenotype is accompanied by modifications of the cytoskeleton such as increased expression of actin and/or tubulin and alterations on the organisation of stress fibres, microtubules and the Golgi complex (Lee et al 1993, Lee 1995, Seidel et al 1995, Erokhina et al 1994. In agreement with these observations, Lucena 1 cells were shown to express higher levels of actin m-RNA and of the proteic subunits a and b-tubulin, when compared to the parental K562 (Trindade et al 1998). It is still unclear the role played by the modifications observed in the cytoskeleton on the MDR phenotype.…”
Section: Alterations Of the Cytoskeletonsupporting
confidence: 70%
“…It must be noted, however, that P-gp inhibition did not systematically restore DOX cytotoxicity in P-gp overexpressing cells (success (Smyth et al, 1998;Fukushima et al, 2000); failure (Campone et al, 2001)). Moreover, cells overexpressing P-gp have also been reported to resist to non-P-gp substrates such as cytosine arabinoside, staurosporine, UV irradiation, Fas receptor ligation and serum starvation (Smyth et al, 1998;Trindade et al, 1999;Campone et al, 2001). Taken together, these findings suggest that other mechanisms of resistance may exist in addition to P-gp overexpression.…”
Section: Introductionmentioning
confidence: 53%
“…Pgp seems to be a target for oxidative damage, a fact we also observed when irradiating MDR leukemia cells with ultraviolet A radiation or treating them with hydrogen peroxide [54]. Thus, PDT can also possibly be used as a modulator of the MDR phenotype, when applied together with chemotherapeutics.…”
Section: Modulation Of the Mdr Phenotype By Pdtmentioning
confidence: 78%